Sosialisasi Strategi Pemasaran Pancake Stroberi Di Kabupaten Karo - Roida Ervina Sinaga; Juliana Br Simbolon; Jupianus Sitepu (STMIK Triguna Dharma, 2022)
Currently marketing activities have a very important role in the business world. So marketing is the whole understanding of sales, trade and distribution. Berastagi, Karo district, is one of the strawberry producing areas in North Sumatera. Service “Socialization of the strawberry Pancake Marketing Strategy”. The purpose of this service is to providesocialization to strawberry pancake enterpreneurs in Berastagi, North Sumatera, about the marketing strategythat is limited to the Berastagi area itself and there are stillfew people who use strawberry pancakes as alivelihood. From the community service activity, it is hoped that participants who participate will be motivated to develop the marketing of the strawberry pancake.Keyword: socialization, marketing, pancake, strawberry